When Students Encounter PISA Questions: From the Perspective of 4C Skills - Simanjuntak, Sinta Dameria; Saragih, Sahat (RANGE: Jurnal Pendidikan Matematika, 2025)
PISA is a prestigious platform for assessing students' learning achievements globally, including 4C skills: creative thinking, critical thinking, communication, and collaboration. However, the 2022 PISA results once again showed disappointing achievements for Indonesia. Indonesian students struggle with solving complex problems (critical thinking), have difficulty conveying ideas effectively (communication), are less prepared for creative challenges (creative thinking), and lack effective collaborative learning approaches. This research aimed to analyze the 4C skills of students at SMP Negeri 31 Medan. The study involved 29 students from class IX-3. Data were collected using two selected essay questions from the 2022 PISA mathematics test, specifically designed to assess 4C skills through indicators like interpreting, formulating, and reasoning. Collaboration was assessed through semi-structured interviews with the class teacher to gain insights into students' interaction and teamwork skills, complementing the written test results. Qualitative descriptive analysis was used to interpret students' written responses, while collaboration data were analyzed based on teacher observations. Assessment criteria followed established indicators for critical thinking (Employ and Evaluate), creativity (formulate), communication (interpret), and collaboration (effective teamwork). The results indicate that 69.56% of students correctly answered interpretation questions (communication, level 3), 39.13% and 43.47% answered employability questions correctly (critical thinking, levels 2 and 1a), and 30.43% correctly answered formulation questions (creativity, level 2). However, teacher observations revealed that students still struggle with effective collaboration, reflecting a broader challenge in fostering teamwork and peer learning. Overall, although communication skills are relatively strong, significant improvements are needed in critical thinking, creativity, and collaboration.